Differential quantitative zinc-induced expression of human metallothionein isogenes in haematopoietic precursor cell lines - Maghdooni Bagheri, Pegah; Rahman, Mohammad Tariqur; Van Soest, Sofie; De Ley, Marc (Elsevier Science B.V., 2009)
The expression pattern of functional members of the metallothionein (MT) gene family was studied in the haematopoietic precursor cell lines, K562, DAMI, MEG-01, and ELF-153 in order to strengthen the proposed function of MT in differentiation. Cells were cultured in RPMI 1640 with 10% (v/v) foetal calf serum, with or without different zinc supplements. Expression of MT isogenes was analysed by quantitative real-time PCR (RT-PCR) using mRNA extracted from cultured cells. The more mature K562, DAMI, and MEG-01 cell lines exhibited transcription of all MT isogenes, except MT-3 and MT-4. Relative quantitative expression of MT isogenes in the mature cell lines such as K562, DAMI, and MEG-01 was higher than in the immature ELF-153 cell line. Immunohistochemical staining (IHC) reveals an increased MT protein biosynthesis in more mature cell lines such as K562, DAMI and MEG-01 greater than in the immature ELF-153 cell line. Real-time PCR and immunohistochemical staining for investigating the effect of phorbol ester and hemin (haematopoietic differentiation stimuli) on expression of MT isogenes in K562 cells reveals that phorbol ester induces increased MT transcription and biosynthesis. Therefore, to our knowledge, the role of MT in differentiation in human haematopoietic precursor cell lines is here reported for the first time.